Technical Note: Motion‐perturbation method applied to dosimetry of dynamic MLC target tracking—A proof‐of‐concept. Issue 11 (7th October 2015) - Feygelman, Vladimir; Tonner, Brian; Stambaugh, Cassandra; Hunt, Dylan; Zhang, Geoffrey; Moros, Eduardo; Nelms, Benjamin E.
Abstract : Purpose: Previous studies show that dose to a moving target can be estimated using 4D measurement‐guided dose reconstruction based on a process called virtual motion simulation, or VMS. A potential extension of VMS is to estimate dose during dynamic multileaf collimator (MLC)‐tracking treatments. The authors introduce a modified VMS method and quantify its performance as proof‐of‐concept for tracking applications. Methods: Direct measurements with a moving biplanar diode array were used to verify accuracy of the VMS dose estimates. A tracking environment for variably sized circular MLC apertures was simulated by sending preprogrammed control points to the MLC while simultaneously moving the accelerator treatment table. Sensitivity of the method to simulated tracking latency (0–700 ms) was also studied. Potential applicability of VMS to fast changing beam apertures was evaluated by modeling, based on the demonstrated dependence of the cumulative dose on the temporal dose gradient. Results: When physical and virtual latencies were matched, the agreement rates (2% global/2 mm gamma) between the VMS and the biplanar dosimeter were above 96%. When compared to their own reference dose (0 induced latency), the agreement rates for VMS and biplanar array track closely up to 200 ms of induced latency with 10% low‐dose cutoff threshold and 300 ms with 50% cutoff. Time‐resolved measurements suggest that even in the modulated beams, the error in the cumulative dose introduced by the 200 ms VMS time resolution is not likely to exceed 0.5%. Conclusions: Based on current results and prior benchmarks of VMS accuracy, the authors postulate that this approach should be applicable to any MLC‐tracking treatments where leaf speeds do not exceed those of the current Varian accelerators.